Personal Support Homes: An Innovative Approach to Reduce the Alternative Level of Care Population in Ontario Hospitals - Eric Nauenberg (Healthcare Policy, 2021)
Objective: This study investigates the viability of personal support homes – a policy concept that reduces alternative level of care (ALC) days in Ontario hospitals. It allows people to leverage their empty bedrooms to temporarily house patients awaiting hospital discharge. Method: Data from the Municipal Property Assessment Corporation are used to map geographic supply of empty bedrooms, and Ontario Ministry of Health administrative data are used to assess potential demand. Results: By remunerating certified homeowners $120–150/day, this concept could help decrease ALC patient days by 20% and save the province $1.13–1.95 billion in foregone hospital construction along with relieving current system pressures. Conclusion: As part of a multifaceted policy solution to ALC, this concept is particularly suited for rural/remote locations where excess bedroom supply per capita is the highest.
Keywords: hospitals, alternative level of care, community care, hallway medicine, long-term care, homecare, personal support homes, Ontario hospitals, hospital discharge